Anaemia Associated with Trypanosomes Infections in Cattle of West Gojjam Zone, Northwest Ethiopia - Kumela Lelisa; Behablom Meharenet (Veterinary Medicine International)
Background. African animal trypanosomosis is a major veterinary problem over a large area of the tsetse belt region of Africa. Anaemia is a cardinal sign of trypanosome infections. The mechanism of anaemia due to trypanosomosis is complex and multifactorial in origin. Packed cell volume (PCV) usually gives an indication of the anaemia and disease status of a trypanosome-infected animal. Methods. A cross-sectional study was conducted from December 2017 to January 2018 in West Gojjam zone, Northwest Ethiopia, to determine the trypanosome infections rate and the possible correlation between parasitic infection and anaemia using the dark ground buffy coat technique, Giemsa-stained thin blood smear, and PCV reading on a haematocrit reader. Results. The overall trypanosomosis prevalence was 7.81%, 95% CI = 7.45–8.17. Trypanosoma congolense (4.25%) and T. vivax (3.56%) were the trypanosomes species identified in the studied area. PCV for all sampled cattle was analysed to estimate the degree of anaemia. From the total examined animals (N = 730), 356 (48.77%) were anaemic and 374 (51.23%) were nonanaemic. The mean PCV of parasitemic cattle was significantly lower (21.09%, 95% CI = 20.13–22.05) than that of aparasitemic ones (25.96%, 95% CI = 25.68–26.24). There was a positive association between trypanosome infection and anaemia. Although both trypanosome species are significantly associated with a decreased herd mean PCV (<24), the mean PCV of cattle infected with T. congolense (19.45%) was lower than that of infected with T. vivax (23.04%). The herd mean PCV was not significantly associated to locations, age, and sex of the studied animals. Conclusions. The study confirms that the prevalence of trypanosomes infections and herd mean PCV has a significant association. The mean herd PCV can be a useful cheap tool to screen for possible trypanosome infection. However, there were cattle positive for trypanosomes having mean PCV within the reference interval and negative animals with anaemia. Furthermore, PCV reading should be confirmed by other diagnostic techniques to accurately conclude that trypanosomosis is the only cause of anaemia.